2010
DOI: 10.1111/j.1365-2958.2010.07245.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic shutdown in Escherichia coli cells lacking the outer membrane channel TolC

Abstract: SummaryThe outer membrane channel TolC is a key component of multidrug efflux and type I secretion transporters in Escherichia coli. Mutational inactivation of TolC renders cells highly susceptible to antibiotics and leads to defects in secretion of protein toxins. Despite impairment of various transport functions, no growth defects were reported in cells lacking TolC. Unexpectedly, we found that the loss of TolC notably impairs cell division and growth in minimal glucose medium. The TolC-dependent phenotype w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
55
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 42 publications
2
55
1
Order By: Relevance
“…3 and Table 2), but the inhibitory effect was very limited for this homolog and is unlikely to have a profound effect on its in vivo activity. The measured cellular concentration of NAD in E. coli is in the range of 0.8 -1.5 mM depending on the growth phase (43), which is at or slightly below the K si NAD for Ugd K-12 (1.4 Ϯ 0.2 mM). The inhibitory effect of NAD at these cellular concentrations will likely impinge on Ugd K-12 activity.…”
Section: Discussionmentioning
confidence: 88%
“…3 and Table 2), but the inhibitory effect was very limited for this homolog and is unlikely to have a profound effect on its in vivo activity. The measured cellular concentration of NAD in E. coli is in the range of 0.8 -1.5 mM depending on the growth phase (43), which is at or slightly below the K si NAD for Ugd K-12 (1.4 Ϯ 0.2 mM). The inhibitory effect of NAD at these cellular concentrations will likely impinge on Ugd K-12 activity.…”
Section: Discussionmentioning
confidence: 88%
“…Taken together, our data demonstrate that TolC affects toxT expression only under certain growth conditions. Recently, a lack of TolC was reported to affect cellular metabolism in E. coli (5), including reports that some metabolites that are exported via TolC modulate gene expression in E. coli (4,20). Thus, we propose that TolC modulates toxT gene expression by modulating TcpP/H activity via accumulation of certain metabolites in V. cholerae.…”
mentioning
confidence: 80%
“…Previous reports indicate that the lack of TolC can induce oxidative stress in E. coli (49). Reasoning that this confounding effect could at least partially account for the apparent U sensitivity of rsaF mutants, we tested whether the deletion of rsaF a leads to an increase in oxidative stress in C. crescentus.…”
Section: Fig 4 Transcript Levels Of Select Gene Candidates In Responsmentioning
confidence: 99%
“…The fact that the rsaF a mutant is sensitive to the detergent SDS is a strong indication that outer membrane barrier function is perturbed in these mutants, directly or indirectly caused by RsaF disruption. Studies in E. coli have also shown that TolC mutants have a variety of pleiotropic effects, including oxidative stress (49,62,63), perturbed peptidoglycan biosynthesis (64), misregulation of outer membrane composition (62,63,65), and aberrant cell morphology under Fe limitation (66). While it is feasible that these pleiotropic effects occur in RsaF mutants, we note that genes involved in oxidative stress or membrane stress were not significantly differentially regulated in the rsaF a mutant compared to levels in the wild type although our analysis was limited to a small subset of genes.…”
Section: Figmentioning
confidence: 99%